Pru p 7 sensitization is a predominant cause of severe, cypress pollen‐associated peach allergy. Issue 4 (19th February 2019) - Klingebiel, Caroline; Chantran, Yannick; Arif‐Lusson, Rihane; Ehrenberg, Angelica E.; Östling, Jonas; Poisson, Alain; Liabeuf, Valérie; Agabriel, Chantal; Birnbaum, Joëlle; Porri, Françoise; Sarrat, Anne; Apoil, Pol‐André; et al.
Abstract: Background: Peach is a common elicitor of food allergic reactions. Peach‐induced immediate reactions may occur as benign pollen‐food syndromes, usually due to birch pollen‐related PR‐10 cross‐reactivity in temperate climates, and as potentially severe primary food allergies, predominantly related to nsLTP Pru p 3 in Mediterranean regions. The newly described peach allergen Pru p 7 has gained recent attention as a potential peach allergy severity marker. Sensitization to Pru p 7 and its allergenic homologues of the gibberellin‐regulated protein family occurs in areas with high Cupressaceae tree pollen exposure. Objective: We sought to investigate the distribution, clinical characteristics and molecular associations of Pru p 7 sensitization among subjects with suspected peach allergy in different regions of France. Methods: Subjects with suspected peach allergy (n = 316) were included. Diagnostic work‐up was performed according to current guidelines, including open food challenge when required. IgE antibody measurements and competition experiments were performed using the ImmunoCAP assay platform. Results: Sensitization to Pru p 7 was present in 171 (54%) of all subjects in the study and in 123 of 198 (62%) diagnosed as peach allergic, more than half of whom were sensitized to no other peach allergen. Frequency and magnitude of Pru p 7 sensitization were associated with the presence of peach allergy, the clinical severity of peach‐induced allergic reactions and the level of cypress pollen exposure. Cypress pollen extract completely outcompeted IgE binding to Pru p 7. Pru p 7 was extremely potent in basophil activation tests. Conclusion and Clinical Relevance: A subtype of Cupressaceae pollinosis, characterized by Pru p 7 sensitization, can be an underlying cause of severe peach allergy.